2017
DOI: 10.5812/zjrms.10197
|View full text |Cite
|
Sign up to set email alerts
|

The Frequency of BCR-ABL1 Fusion Transcripts in Iranian Patients with Three Different Types of Leukemia

Abstract: Background: Different BCR-ABL fusion transcripts occur more or less frequently, in three different types of leukemia Objectives: This study was done to determine the frequencies of BCR-ABL fusion transcripts in leukemia patients from Iran. Methods: This experimental study was carried out from 2001 to 2015 in Pasteur Institute of Iran. The leukemia patients containing 348 chronic myeloid leukemia (CML), 72 acute lymphoblastic leukemia (ALL), and 34 acute myeloid leukemia (AML) were studied. Total RNA was extrac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 15 publications
0
3
0
Order By: Relevance
“…However, Al‐Achkar, Moassass, Youssef, and Wafa (), Hanfstein et al () and Hamid and Bokharaei () did not catch any association between gender and BCR‐ABL transcripts. Furthermore, other studies registered reversed setting, that is, b3a2 transcript was more common in females and b2a2 transcript was more common in males.…”
Section: Discussionmentioning
confidence: 93%
“…However, Al‐Achkar, Moassass, Youssef, and Wafa (), Hanfstein et al () and Hamid and Bokharaei () did not catch any association between gender and BCR‐ABL transcripts. Furthermore, other studies registered reversed setting, that is, b3a2 transcript was more common in females and b2a2 transcript was more common in males.…”
Section: Discussionmentioning
confidence: 93%
“…The frequency of BCR ABL gene in acute lymphoblastic leukemia in our study population is comparable to international studies. [8][9][10][11][12][13] However, it is the largest first-ofits-kind study in Pakistan, conducted in AFIP center.…”
Section: Discussionmentioning
confidence: 99%
“…7 Another study was conducted at Pasteur Institute Iran on 72 patients of ALL in which 9 (12.5%) patient of ALL were positive for BCR-ABL gene rearrangement. 8 These studies being conducted on small sample size showed variation in the results hence we carried out our study in our institute on a large sample size to see the frequency of BCR-ABL gene mutation in diagnosed patients of acute lymphoblastic leukemia.…”
Section: Original Articlementioning
confidence: 99%